Resin composition, binder resin, polymer thin film and battery
Patent Information
- Application Number
- JP2024559708
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-31
- Filing Date
- 2024-03-14
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2044-03-14
Smart Images

Figure 0007644875000016 
Figure 0007644875000017 
Figure 0007644875000018
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a binder resin, a polymer thin film, and a battery. [Background technology]
[0002] Polycarbonate is used in various applications, for example, as a material in the battery field. Binder resins containing polycarbonate are used, for example, as binding agents for forming electrodes. Polymer thin films containing polycarbonate are used, for example, as battery separators. For example, Patent Document 1 discloses a polymer binder containing a three-dimensional cross-linked aliphatic polycarbonate. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2020 / 203882 Summary of the Invention [Problem to be solved by the invention]
[0004] The polymer binder described in Patent Document 1 is a binder for solid electrolytes and is not intended for use in batteries using electrolytic solutions. Therefore, when an electrode made using this polymer binder is used in a battery using electrolytic solutions, there is a risk of a problem in that the polymer binder dissolves into the electrolytic solution.
[0005] An object of the present invention is to provide a crosslinkable resin composition, a binder resin, a polymer thin film, and a battery. [Means for solving the problem]
[0006] [1] A copolymer containing a constitutional unit represented by the following general formula (1) and a constitutional unit represented by the following general formula (2) in an amount of 0.3 mol% to 20.0 mol%: Resin composition.
[0007] [ka]
[0008] (In the general formula (1) and the general formula (2), R 1 is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and L 1 and L 2 each independently represents a single bond or an alkylene group having 1 to 3 carbon atoms; 1 is any one of the reactive groups represented by the following structural formula (2-1) and the following structural formula (2-2).
[0009] [ka]
[0010] [2] The resin composition according to [1], The copolymer further contains at least one structural unit selected from the group consisting of structural units represented by the following general formula (3) and structural units represented by the following general formula (4), in an amount of 0.1 mol % to 30.0 mol %: Resin composition.
[0011] [ka]
[0012] (In the general formula (3) and the general formula (4), R 2 is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and L 3 and L 4 each independently represents a single bond or an alkylene group having 1 to 3 carbon atoms; 2is any one of the reactive groups represented by the following structural formula (4-1) and the following structural formula (4-2).
[0013] [ka]
[0014] [3] The resin composition according to [1] or [2], The crosslinked product of the resin composition is the amount of the copolymer eluted in ethyl acetate is 10% or less; The swelling ratio of the copolymer in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 is 100% or more. Resin composition.
[0015] [4] The resin composition according to any one of [1] to [3], Binder resin.
[0016] [5] The binder resin according to [4] is contained. battery.
[0017] [6] The resin composition according to any one of [1] to [3], Polymer thin film.
[0018] [7] [6] The polymer thin film according to the present invention is included. battery.
[0019] According to one aspect of the present invention, it is possible to provide a crosslinkable resin composition, a binder resin, a polymer thin film, and a battery. [Brief description of the drawings]
[0020] [Figure 1] 1 is a cross-sectional view illustrating an example of a main part of a battery according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram for explaining the action and effect when the polymer thin film according to the present embodiment is used as a battery separator. [Diagram 3] 1 is a chart showing the results of 1H-NMR measurement of the copolymer produced in Example 1. [Figure 4] 1 is a chart showing the results of 1H-NMR measurement of the copolymer produced in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The present invention will be described below by taking an embodiment as an example, but the present invention is not limited to the content of the embodiment.
[0022] [Resin composition] A preferred example of the resin composition according to this embodiment will be described.
[0023] The resin composition according to this embodiment contains a copolymer containing a constitutional unit represented by general formula (1) and 0.3 mol % or more and 20.0 mol % or less of a constitutional unit represented by general formula (2).
[0024] According to the resin composition of the present embodiment, the resin composition has the above-mentioned structure, and thus has crosslinking properties. In addition, by using the resin composition of the present embodiment, a binder resin having excellent adhesion to metal foil and binding properties to inorganic materials can be obtained. In addition, by using the resin composition of the present embodiment, a polymer thin film having high swelling properties in an electrolyte solution or the like can be obtained. For example, when the resin composition according to the present embodiment is used as a material in the field of batteries, the copolymer used in the resin composition according to the present embodiment has a carbonate skeleton as the main polymer skeleton, which improves compatibility with the electrolyte. Therefore, when assembling a battery, the polymer thin film as a separator can be swollen after the electrolyte is injected. By containing 0.3 mol % or more and 20.0 mol % or less of the constitutional unit represented by the general formula (2) having a reactive group, the crosslinking reaction proceeds appropriately, making it possible to achieve both a high degree of swelling and a low amount of elution.
[0025] The resin composition according to the present embodiment may contain other components as long as it contains the specific copolymer having the above-mentioned structure, as long as the object of the present invention is not impaired.
[0026] (copolymer) The copolymer contained in the resin composition according to this embodiment includes a copolymer containing a constitutional unit represented by the following general formula (1) and 0.3 mol % or more and 20.0 mol % or less of a constitutional unit represented by the following general formula (2).
[0027] [ka]
[0028] In the general formula (1) and the general formula (2), R 1 is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, preferably a hydrogen atom or a methyl group, and particularly preferably a methyl group. L 1 and L 2 are each independently a single bond or an alkylene group having 1 to 3 carbon atoms, preferably a methylene group or an ethylene group, and particularly preferably a methylene group. X 1 is any one of the reactive groups represented by the following structural formula (2-1) and the following structural formula (2-2): In addition, the wavy line in the structural formula indicates a bond position.
[0029] [ka]
[0030] Such a copolymer may be a random copolymer or a block copolymer, but from the viewpoint of ease of synthesis, the copolymer is preferably a random copolymer.
[0031] The copolymer contained in the resin composition according to this embodiment has, for example, the following composition ratio when it is a copolymer composed of a constitutional unit represented by general formula (1) and a constitutional unit represented by general formula (2). The ratio of the structural unit represented by the general formula (2) must be 0.3 mol% or more and 20 mol% or less with respect to all structural units. If this ratio is less than 0.3 mol%, the amount of elution will be high. On the other hand, if this ratio exceeds 20.0 mol%, the crosslink density of the copolymer will be high, resulting in a problem of reduced swelling. From the same viewpoint, the ratio of the constitutional unit represented by the general formula (2) is preferably 1.0 mol% or more, more preferably 1.5 mol% or more, and even more preferably 1.8 mol% or more. On the other hand, the ratio of the constitutional unit represented by the general formula (2) is preferably 19.0 mol% or less, more preferably 18.0 mol% or less, even more preferably 12.0 mol% or less, and particularly preferably 6.0 mol% or less.
[0032] The ratio of the structural unit represented by general formula (1) is required to be 80.0 mol% or more and 99.7 mol% or less with respect to all structural units. The ratio of the structural unit represented by general formula (1) is preferably 81.0 mol% or more, more preferably 82.0 mol% or more, even more preferably 88.0 mol% or more, and particularly preferably 94.0 mol% or more. On the other hand, the ratio of the structural unit represented by general formula (1) is preferably 99.0 mol% or less, more preferably 98.5 mol% or less, and even more preferably 98.2 mol% or less.
[0033] The copolymer contained in the resin composition according to this embodiment preferably further contains at least one structural unit selected from the group consisting of structural units represented by the following general formula (3) and structural units represented by the following general formula (4), in an amount of 0.1 mol % to 30.0 mol %: By forming a copolymer containing an ether skeleton such as the structural unit represented by general formula (3) or (4), the glass transition temperature of the copolymer is lowered and the thin film becomes flexible, which is expected to result in high ionic conductivity.
[0034] [ka]
[0035] In the general formula (3) and the general formula (4), R 2 is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, preferably a hydrogen atom or a methyl group, and particularly preferably a methyl group. L 3 and L 4 are each independently a single bond or an alkylene group having 1 to 3 carbon atoms, preferably a methylene group or an ethylene group, and particularly preferably a methylene group. X 2 is any one of the reactive groups represented by the following structural formula (4-1) and the following structural formula (4-2): In addition, the wavy line in the structural formula indicates a bond position.
[0036] [ka]
[0037] The copolymer contained in the resin composition according to the present embodiment has, for example, the following composition ratio when it is a copolymer composed of a constitutional unit represented by general formula (1), a constitutional unit represented by general formula (2), a constitutional unit represented by general formula (3), and a constitutional unit represented by general formula (4). The ratio of the constitutional units represented by the general formula (2) is as described above. The total ratio of the structural unit represented by general formula (3) and the structural unit represented by general formula (4) is preferably 0.1 mol% or more and 30.0 mol% or less with respect to all structural units.If the total ratio of these is less than 0.1 mol%, the effect of the ether skeleton tends not to be fully exerted.On the other hand, if the total ratio of these is more than 30.0 mol%, the compatibility with the electrolyte solution tends to be poor, the swelling degree tends to decrease, and the ion conductivity tends to decrease. From the same viewpoint, the total ratio of these is preferably 1.0 mol% or more, and more preferably 2.0 mol% or more, while the total ratio of these is preferably 25.0 mol% or less, more preferably 20.0 mol% or less, and particularly preferably 10.0 mol% or less.
[0038] The ratio of the structural unit represented by general formula (1) is preferably 50.0 mol% or more and 99.6 mol% or less with respect to all structural units. The ratio of the structural unit represented by general formula (1) is preferably 55.0 mol% or more, more preferably 60.0 mol% or more. On the other hand, the ratio of the structural unit represented by general formula (1) is preferably 98.0 mol% or less, more preferably 94.0 mol% or less.
[0039] The molecular weight of the copolymer according to this embodiment, measured by the method shown in the measurement example, is preferably 5,000 or more and 5,000,000 or less, and more preferably 10,000 or more and 1,000,000 or less, when expressed as a weight average molecular weight (Mw). Furthermore, the molecular weight of the copolymer according to this embodiment, measured by the method shown in the measurement example, is preferably 3,000 or more and 3,000,000 or less, and more preferably 5,000 or more and 500,000 or less, when expressed as a number average molecular weight (Mn). In addition, the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) is preferably 1 or more and 10 or less, more preferably 1.1 or more and 5 or less. When the molecular weight and molecular weight distribution of the copolymer are in the above ranges, sufficient handleability can be obtained when the copolymer is formed into a film. Furthermore, when the copolymer is used as a binder, when the molecular weight and molecular weight distribution of the copolymer are in the above ranges, the viscosity of the slurry becomes appropriate when preparing an electrode slurry, the sedimentation of the active material and conductive assistant is suppressed, and sufficient dispersibility of the active material and conductive assistant can be obtained.
[0040] (Method of Producing Copolymer) The method for producing the copolymer contained in the resin composition according to the present embodiment is not particularly limited, and the copolymer can be obtained by a known method. For example, the copolymer can be produced by the following method. As described in the Examples below, it can be produced by copolymerizing an epoxide monomer such as propylene oxide with carbon dioxide in the presence of a polymerization catalyst. Specifically, propylene oxide undergoes ring-opening to become a constitutional unit represented by general formula (3), and a part of propylene oxide undergoes ring-opening polymerization with carbon dioxide to become a constitutional unit represented by general formula (1).
[0041] The polymerization catalyst used in producing the copolymer is not particularly limited, and examples thereof include metal salen complex catalysts such as cobalt salen catalysts, and organozinc catalysts.
[0042] The amount of the polymerization catalyst used in the copolymerization reaction of the epoxide monomer with carbon dioxide, for example, in the case of a metal-salen complex catalyst, is preferably 0.05 mol or less, more preferably 0.01 mol or less, and particularly preferably 0.001 mol or less, per 1 mol of the epoxide monomer. Furthermore, when using a metal salen complex catalyst, a co-catalyst can be used. As the co-catalyst, for example, an onium salt compound is preferable. Specific examples of the onium salt compound are not particularly limited, but from the viewpoint of having high reaction activity, bis(triphenylphosphoranylidene)ammonium chloride, piperidine, bis(triphenylphosphoranylidene)ammonium fluoride, ammonium pentafluorobenzoate, and tetra-n-butylammonium chloride are preferable.
[0043] Incidentally, the optimum polymerization conditions vary depending on the type of catalyst, but for example, the pressure of carbon dioxide in the reaction vessel is 0.1 MPa or more and 10 MPa or less, preferably 0.5 MPa or more and 5 MPa or less. Furthermore, in the case of a cobalt salen complex catalyst, for example, the polymerization temperature is preferably about room temperature (25° C.) from the viewpoint of good catalytic activity and accelerated reaction rate.
[0044] In the method of copolymerizing an epoxide monomer with carbon dioxide, examples of the epoxide monomer used as a starting material include ethylene oxide, propylene oxide, 1,2-butylene oxide, allyl glycidyl ether, and 4-hydroxybutyl acrylate glycidyl ether. Note that the molar ratio of the constitutional unit represented by general formula (1) and the constitutional unit represented by general formula (2) in the copolymer may not match the molar mixing ratio of the epoxide monomer serving as the starting material for the constitutional unit represented by general formula (1) and the epoxide monomer serving as the starting material for the constitutional unit represented by general formula (2) due to differences in reactivity.
[0045] (Characteristics of the crosslinked product of the resin composition) In the crosslinked product of the resin composition according to the present embodiment, the amount of copolymer eluted in ethyl acetate is preferably 40% or less, more preferably 30% or less, even more preferably 20% or less, particularly preferably 10% or less, and very preferably 7% or less. The amount of eluted copolymer is preferably as low as possible because the eluted low molecular weight component becomes an irreversible capacity. The lower limit of the amount of eluted copolymer is not particularly limited, and may be, for example, 1% or more, 0.1% or more, or 0%.
[0046] In the crosslinked product of the resin composition according to this embodiment, it is preferable that the amount of the copolymer eluted into ethyl acetate is within the above range, and the degree of swelling of the copolymer in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 is 100% or more.
[0047] The crosslinked product of the resin composition according to the present embodiment preferably has high swelling properties in the electrolyte and the carbonate-based solvent used as the electrolyte solvent. From this viewpoint, the swelling degree of the copolymer in the mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 is preferably 100% or more, more preferably 200% or more, even more preferably 300% or more, particularly preferably 500% or more, very preferably 700% or more, and most preferably 900% or more. The upper limit of this swelling degree is not particularly limited, and may be, for example, 2000% or less.
[0048] (Method of Crosslinking Resin Composition) In the resin composition according to the present embodiment, a photopolymerization initiator is preferably used from the viewpoint of easily obtaining a polymer thin film in which the copolymer is crosslinked. When a photopolymerization initiator is used in the resin composition according to the present embodiment, the thin film containing the copolymer is crosslinked by reaction of reactive groups (allyl group and (meth)acryloyl group) in the side chain of the copolymer in the thin film.
[0049] The photopolymerization initiator is not particularly limited, and may be a known compound. The photopolymerization initiator is preferably a photopolymerization initiator that is sensitive to ultraviolet light. The photopolymerization initiator may be used alone or in combination of two or more kinds.
[0050] Specific examples of the photopolymerization initiator include α-ketol compounds such as 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, α-hydroxy-α,α'-dimethylacetophenone, 2-methyl-2-hydroxypropiophenone, and 1-hydroxycyclohexylphenyl ketone; acetophenone compounds such as methoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxyacetophenone, and 2-methyl-1-[4-(methylthio)-phenyl]-2-morpholinopropane-1; benzoin ether compounds such as benzoin ethyl ether, benzoin isopropyl ether, and anisoin methyl ether; aromatic sulfonyl chloride compounds such as 2-naphthalenesulfonyl chloride; photoactive oxime compounds such as 1-phenone-1,1-propanedione-2-(o-ethoxycarbonyl)oxime; benzophenones such as benzoylbenzoic acid and 3,3'-dimethyl-4-methoxybenzophenone; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, and 2-methylthioxanthone; benzophenone compounds such as camphorquinone; halogenated ketones, acylphosphinoxides, acylphosphonates, and oligo[2-hydroxy-2-methyl-1-(4-(1-methylvinyl)phenyl)propanone].
[0051] The content of the photopolymerization initiator is, for example, preferably 0.1 parts by mass or more and 10 parts by mass or less, more preferably 0.5 parts by mass or more and 7.5 parts by mass or less, and even more preferably 1 part by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the copolymer.
[0052] The resin composition according to the present embodiment is molded into a predetermined shape, and the molded product is irradiated with energy rays to crosslink the copolymer, thereby obtaining a thin film that is a crosslinked product of the copolymer. The type of energy rays is not particularly limited, but ultraviolet rays are preferred in terms of reactivity and workability. The device for irradiating the molded product with ultraviolet rays is not particularly limited, and may be, for example, a device equipped with an ultraviolet LED lamp, a device equipped with a high-pressure mercury lamp, or a device equipped with a metal halide lamp.
[0053] The conditions for irradiating the molded product with ultraviolet light are not particularly limited. The maximum illuminance and the integrated light quantity when irradiating the molded product with ultraviolet light are, for example, as follows: Maximum illuminance: 5 mW / cm 2 More than 1000mW / cm 2 The integrated light quantity is preferably 50 mJ / cm or less. 2 More than 5000mJ / cm 2 It is preferable that:
[0054] [Binder resin] The binder resin according to the present embodiment contains the resin composition according to the present embodiment. When the binder resin according to the present embodiment is used as a material for a composite layer in an electrode of a secondary battery, the binder resin according to the present embodiment has excellent swelling properties with respect to an electrolytic solution, and has excellent adhesion to a metal foil and binding properties for inorganic materials. The reason for this is unclear, but is considered to be as follows.
[0055] Conventional binder resins, when used in the composite layer of secondary batteries such as lithium ion batteries, have been designed to have low swelling properties in response to an electrolyte, so that even if the binder resin swells with the electrolyte, it is possible to obtain adhesion between the composite layer and the current collector and binding between the active materials in the composite layer. It is considered that the composite layer in contact with the electrolyte has a contact area between the binder resin and the active material, and a contact area between the active material and the electrolyte, due to the electrolyte permeating into the composite layer. Conventional binder resins have low swelling properties with respect to the electrolyte, so that ionic conductivity is difficult to be expressed, and the ionic conductivity of lithium ions and the like contained in the electrolyte is low in the contact area between the binder resin and the active material. On the other hand, the ionic conductivity of lithium ions and the like contained in the electrolyte is improved in the contact area between the active material and the electrolyte. In addition, conventional binder resins have low swelling properties with respect to the electrolyte, so the area of the contact area between the binder resin and the active material does not expand much, and while the contact area is small, the area of the contact area between the active material and the electrolyte is large. Although it is considered that the electrolyte is unlikely to decompose in the contact area between the binder resin and the active material, a decomposition layer of the electrolyte, called a solid electrolyte interphase (SEI) layer, is likely to form in the contact area between the active material and the electrolyte. When a conventional binder resin is used in the composite layer, as described above, the area of the contact area between the active material and the electrolyte is large, and therefore the area on which the SEI layer is formed is also large, which tends to shorten the life of the electrolyte.
[0056] In contrast, when the binder resin according to the present embodiment is used in a composite layer of a secondary battery such as a lithium ion battery, the binder resin according to the present embodiment has high swelling property with respect to the electrolyte solution because it contains a copolymer having a carbonate skeleton as the main polymer skeleton, and thus has improved compatibility with the electrolyte solution. The binder resin according to the present embodiment swells greatly upon contact with the electrolyte solution, thereby exhibiting ion conductivity. In addition, since the binder resin according to the present embodiment has high swelling property with respect to the electrolyte solution, the area of the contact region between the binder resin and the active material is increased, while the area of the contact region between the active material and the electrolyte solution is reduced. For this reason, when the binder resin according to the present embodiment is used, the contact region between the binder resin and the active material is considered to exhibit ion conductivity and the electrolyte solution is difficult to decompose, and the area in which the SEI layer is formed is considered to be suppressed in the contact region between the active material and the electrolyte solution. As a result, when the binder resin according to the present embodiment is used in a composite layer of a secondary battery such as a lithium ion battery, it is considered to contribute to improving the life of the electrolyte solution, which is considered to result in improved battery performance. However, if the swelling property with respect to the electrolyte is too high, the adhesion to the metal foil and the binding property of the inorganic material tend to decrease.
[0057] The binder resin according to the present embodiment has excellent adhesion to metal foil and binding ability to inorganic materials, and can be applied to applications requiring such characteristics. The binder resin according to the present embodiment is preferably applied to battery applications, for example. In this case, the binder resin according to the present embodiment is preferably a binder resin for battery electrodes, and is also preferably a binder resin for electrodes of secondary batteries such as lithium ion batteries. The binder resin according to the present embodiment may be applied as a binder resin used in a composite layer in a positive electrode, or may be applied as a binder resin used in a composite layer in a negative electrode.
[0058] [Polymer thin film] The polymer thin film according to the present embodiment contains the resin composition according to the present embodiment. According to the polymer thin film according to the present embodiment, a polymer thin film having high swelling properties in an electrolyte solution or the like can be obtained. The reason is unclear, but is thought to be as follows. The copolymer used in the polymer thin film according to the present embodiment has a carbonate skeleton as the main polymer skeleton, which improves compatibility with the electrolyte solution. Therefore, when assembling a battery, the polymer thin film as a separator can be swollen after the electrolyte solution is injected. And, by containing a predetermined amount of a constitutional unit represented by general formula (2) having a reactive group, the crosslinking reaction proceeds appropriately, so that it is possible to achieve both a high degree of swelling and a low amount of elution.
[0059] The polymer thin film according to the present embodiment has high swelling properties in an electrolyte solution or the like, and can be applied to applications requiring such properties. The polymer thin film according to the present embodiment is preferably applied to, for example, battery applications. In this case, the polymer thin film according to the present embodiment is preferably, for example, a battery separator, and is also preferably a battery separator for a secondary battery such as a lithium ion battery. The polymer thin film according to the present embodiment is also preferably, for example, an anode protective film that covers at least a part of the anode of a battery, and is also preferably an anode protective film for a secondary battery such as a lithium ion battery.
[0060] [battery] Next, a preferred example of the battery according to this embodiment will be described.
[0061] The battery according to the present embodiment is a battery to which the resin composition according to the present embodiment is applied. The battery according to the present embodiment includes the binder resin according to the present embodiment as a material constituting the electrodes of the battery. The battery according to the present embodiment also includes the polymer thin film according to the present embodiment as, for example, a battery separator. The battery is composed of a positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode. By adopting such a configuration, a battery excellent in each characteristic can be obtained. In addition, the battery is preferably a secondary battery, and more preferably a secondary battery such as a lithium ion battery. The structure of the battery according to the present embodiment is not particularly limited, and may be a stacked structure or a wound structure.
[0062] Here, an example of a battery using the polymer thin film according to the present embodiment will be described with reference to the drawings. In the drawings, some parts are illustrated enlarged or reduced in size for ease of explanation.
[0063] FIG. 1 shows an example of a battery using the polymer thin film according to the present embodiment. The battery 100 shown in FIG. 1 is a lithium ion secondary battery. As shown in FIG. 1, the battery 100 includes a positive electrode 10, a negative electrode 20, and an electrolyte layer 30 between the positive electrode 10 and the negative electrode 20. The positive electrode 10 is composed of a positive electrode current collector 13 and a positive electrode composite layer 11 laminated on the positive electrode current collector 13, and the negative electrode 20 is composed of a negative electrode current collector 23 and a negative electrode composite layer 21 laminated on the negative electrode current collector 23. The electrolyte layer 30 is composed of an electrolyte 33 and a separator 31 impregnated with the electrolyte 33, and the separator 31 separates the positive electrode 10 side from the negative electrode 20 side. The battery 100 has a laminated structure in which a positive electrode current collector 13, a positive electrode composite layer 11, an electrolyte layer 30, a negative electrode composite layer 21, and a negative electrode current collector 23 are laminated in this order from the positive electrode current collector 13 toward the negative electrode current collector 23, and the laminated structure is contained inside a container not shown. In the battery 100, the positive electrode mixture layer 11 and the negative electrode mixture layer 21 preferably contain a binder resin (not shown) according to this embodiment. In this case, the positive electrode mixture layer 11 and the negative electrode mixture layer 21 contain the electrolyte solution 33 due to the electrolyte solution 33 of the electrolyte layer 30 permeating therein, and the binder resin according to this embodiment (not shown) is swelled by the electrolyte solution 33. In the battery 100, the polymer thin film according to this embodiment is preferably used as the separator 31. In battery 100, the polymer thin film according to this embodiment is preferably used as a negative electrode protective film (not shown) that covers at least a portion of negative electrode mixture layer 21.
[0064] According to the battery using the polymer thin film of this embodiment, the above-mentioned configuration can suppress the generation of dendrites. The reason is unclear, but it is thought to be as follows. When the polymer thin film of this embodiment is used as the separator 31, when assembling the battery, after the electrolyte is injected, the separator 31 and the electrolyte 33 are separated as shown in FIG. 2(A). In this state, a gap due to fine irregularities exists between the negative electrode mixture layer 21 and the separator 31. The inventors presume that dendrites are precipitated in this portion. On the other hand, the separator 31 using the polymer thin film of this embodiment has high swelling property in the electrolyte 33, so that the separator 31 swells as shown in FIG. 2(B) after a certain time has passed after the electrolyte is injected. Then, due to such swelling of the separator 31, the gap between the negative electrode mixture layer 21 and the separator 31 disappears as shown in FIG. 2(C). Therefore, when the polymer thin film of this embodiment is used as the separator 31, the generation of dendrites can be suppressed.
[0065] Although an example of the battery according to the present embodiment has been described above with reference to Fig. 1 and Fig. 2, the example of the battery according to the present embodiment is not limited thereto. The battery according to the present embodiment may adopt various forms as long as the polymer thin film according to the present embodiment is used.
[0066] Examples of materials used for the positive electrode current collector and the negative electrode current collector include metal foils or metal plates such as copper, aluminum, nickel, titanium, and stainless steel, as well as carbon sheets and carbon nanotube sheets.
[0067] The positive electrode mixture layer is preferably composed of, for example, a positive electrode active material such as a lithium-containing composite oxide, a conductive assistant such as a carbon-based material, and the binder resin according to the present embodiment.
[0068] The negative electrode mixture layer is preferably composed of a negative electrode active material such as acetylene black, carbon nanotubes, carbon nanofibers, graphene, etc., and the binder resin according to the present embodiment.
[0069] The electrolyte layer is preferably composed of, for example, an electrolyte solution and a separator which is a polymer thin film according to this embodiment.
[0070] In the battery according to the present embodiment, the electrolyte preferably contains a lithium salt and a carbonate-based solvent. In order to easily improve the effect of suppressing the generation of dendrites, the molar ratio of the lithium salt to the carbonate-based solvent (the lithium salt / the carbonate-based solvent) is preferably 1 / 6 or more and 1 / 1 or less. This molar ratio is more preferably 1 / 4 or more and 1 / 1 or less, and even more preferably 1 / 3 or more and 1 / 1 or less.
[0071] Specific examples of lithium salts include lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium 2-trifluoromethyl-4,5-dicyanoimidazolate, lithium 4,5-dicyano-1,2,3-triazolate, lithium bis(pentafluoroethylsulfonyl)imide, lithium borofluoride, lithium bis(oxalato)borate, lithium nitrate, lithium chloride, lithium bromide, and lithium fluoride. The lithium salt may be one or more of these exemplified lithium salts.
[0072] Examples of the carbonate-based solvent include dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethylene carbonate, propylene carbonate, and butylene carbonate. The carbonate-based solvent can be one or more of these lithium salts. Here, the carbonate-based solvent in this embodiment refers to a compound having a carbonate skeleton in its molecular structure.
[0073] The present invention is not limited to the above-described embodiment, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention. EXAMPLES
[0074] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples in any way.
[0075] Measurements and evaluations in the following Examples and Comparative Examples were carried out by the methods described below.
[0076] [Measurement of weight average molecular weight (Mw) and number average molecular weight (Mn)] Measurements were carried out under the following conditions using a gel permeation chromatograph (manufactured by Tosoh Corporation, product name "HLC-8320GPC"), and the values measured were converted into standard polystyrene equivalent values. (Measurement conditions) Column: "TSKgel guardcolumn SuperH-H", "TSKgel SuperHM-H", "TSKgel SuperHM-H", and "TSKgel SuperH2000" (all manufactured by Tosoh Corporation) connected in series Column temperature: 40°C Developing solvent: Tetrahydrofuran (copolymer concentration 1% by mass) Standard material: polystyrene ·Injection volume: 20μL ·Flow rate: 0.60mL / min Detector: Differential refractometer
[0077] [Measurement of elution amount] The thin film obtained in each of the examples and comparative examples described below was weighed to about 300 mg. The mass of the thin film at this time was defined as M0. The thin film was wrapped in a polyester mesh (mesh size 200). The mass of the thin film wrapped in the polyester mesh was weighed, and the mass of the thin film was subtracted to calculate the mass of the polyester mesh alone. Next, the thin film wrapped in the polyester mesh was immersed in ethyl acetate at 23°C for 48 hours. Thereafter, the thin film wrapped in the polyester mesh was taken out of the ethyl acetate, dried in an oven at 120°C for 2 hours, and further air-dried for 2 hours in an environment at a temperature of 23°C and a relative humidity of 50%. The mass after the air drying was weighed, and the mass of the thin film alone after immersion was calculated by subtracting the mass of the polyester mesh alone. The mass at this time was defined as M1. The amount of elution was calculated using the following formula (F1). Elution amount (%)={(M0-M1) / M0}×100 (F1) In formula (F1), M0 represents the mass of the thin film weighed before being wrapped in the polyester mesh, and M1 represents the mass of the thin film alone after being immersed in ethyl acetate.
[0078] [Swelling degree measurement] The thin film obtained in each of the examples and comparative examples described below was cut to about 3 cm (vertical) x about 3 cm (horizontal), and the obtained thin film piece was weighed to be about 1 g. The mass at this time was defined as W0. The thin film piece was wrapped in a polyester mesh (mesh size 200), and the mass of the thin film piece wrapped in the polyester mesh was weighed, and the mass of the thin film piece was subtracted to calculate the mass of the polyester mesh alone. The thin film was immersed in a carbonate-based solvent [composition: mixed solvent of ethylene carbonate / dimethyl carbonate = 1 / 1 (volume ratio)] for 24 hours to cause swelling. Thereafter, the thin film piece wrapped in the polyester mesh was pulled out, the solvent on the surface was wiped with a paper wiper, and the mass was measured, and the mass of the swollen thin film piece was calculated by subtracting the mass of the polyester mesh alone. The mass at this time was defined as W1. The swelling degree was calculated using the following formula (F2). Swelling degree (%) = {(W1-W0) / W0} × 100 (F2) In formula (F2), W0 represents the mass of the thin film piece weighed before being wrapped in the polyester mesh, and W1 represents the mass of only the thin film piece after swelling.
[0079] [Ionic conductivity measurement] The lithium half-cells obtained in each of the Examples and Comparative Examples described below were measured using an AC impedance method in which an AC voltage (applied voltage of 10 mV) is applied between the electrodes to measure the resistance component. The ionic conductivity was calculated from the real impedance intercept of the obtained Cole-Cole plot. A potentiostat / galvanostat (VMP-300, manufactured by Biologic) was used for the measurements. Ionic conductivity (σ A ) was calculated using the following formula (F3). σ A =L A / (R A ×S A ) (F3) In formula (F3), σ A is the ionic conductivity (unit: S cm -1 ), R A is resistance (unit: Ω), S A is the cross-sectional area of the solid electrolyte membrane at the time of measurement (unit: cm 2 ), L A indicates the distance between electrodes (unit: cm). The measurement temperature was 25°C. The ionic conductivity (σ A ) was calculated.
[0080] [Example 1] (Synthesis of Polymerization Catalyst) (R,R)-N,N'-bis(3,5-di-tert-butylsalicylidene)-1,2-diaminocyclohexanecobalt(II) and pentafluorobenzoic acid were weighed out to a molar ratio of 1:1.1 and placed in a flask, to which was added dehydrated toluene. The flask was shielded from light with aluminum foil and allowed to react at room temperature for 20 hours. The chemical reaction formula is as follows. After the reaction was completed, the solvent was removed under reduced pressure and the mixture was washed several times with an excess amount of hexane. It was then vacuum dried at room temperature to obtain a cobalt salen complex.
[0081] [ka]
[0082] (Synthesis of Copolymer A) As the epoxide monomer, a mixture of propylene oxide and allyl glycidyl ether in a molar ratio of 97:3 was used, and the synthesized cobalt salen complex as the polymerization catalyst and bis(triphenylphosphoranylidene)ammonium chloride as the cocatalyst were weighed out in a molar ratio of epoxide monomer:catalyst:cocatalyst = 2000:1:1 and placed in a pressure vessel. Furthermore, after adding 200 ppm of phenothiazine, ethyl acetate was added so that the monomer:ethyl acetate = 50:50 (mass ratio). All of these operations were performed by replacing the inside of the pressure vessel with argon. Next, after purging the inside of the pressure vessel, carbon dioxide was introduced into the pressure vessel by a liquid pump, the pressure in the pressure vessel was set to 2.0 MPa, and the polymerization reaction was carried out at 25 ° C for 20 hours. After the reaction was completed, chloroform was added to the contents of the pressure vessel to prepare a chloroform solution, and 1M hydrochloric acid was added. Next, the chloroform solution was dropped into stirred methanol to precipitate the product. The product was then dried under reduced pressure in a desiccator using a diaphragm pump, and then vacuum dried at 60°C to obtain copolymer A.
[0083] The structure of the obtained copolymer A was confirmed by nuclear magnetic resonance spectroscopy ( 1When H-NMR (Biospin Avance 500, Bruker) was used with a solvent (CDCl3, containing 0.03 volume% tetramethylsilane), the molar ratio of the structural unit represented by general formula (1) (hereinafter also referred to as structural unit (1)), the structural unit represented by general formula (2) (hereinafter also referred to as structural unit (2)), the structural unit represented by general formula (3) (hereinafter also referred to as structural unit (3)), and the structural unit represented by general formula (4) (hereinafter also referred to as structural unit (4)) in copolymer A was structural unit (1):structural unit (2):structural unit (3):structural unit (4)=94.5:2.9:2.5:0.1 (see FIG. 3). The number average molecular weight Mn of the resulting copolymer A was 24,000, and the molecular weight distribution Mw / Mn was 1.1.
[0084] (Preparation of thin films) To the obtained copolymer A, 1-hydroxycyclohexyl phenyl ketone was added as a photopolymerization initiator so that the copolymer: initiator = 97: 3 mass%, and further diluted with ethyl acetate and stirred to prepare a solution for thin film formation with a solid content concentration of 30 mass%. A first release film (manufactured by Lintec Corporation, product name "SP-PET381031") was prepared, and the prepared solution for thin film formation was applied to the release-treated surface of this release film, and dried at 120 ° C for 1 minute to form a thin film layer with a thickness of 10 μm. Furthermore, a second release film (manufactured by Lintec Corporation, product name "SP-PET382150") was prepared, and the release-treated surface of this release film was attached to the surface of the thin film layer. Thereafter, the thin film laminate sandwiched between the first release film and the second release film was placed on a stainless steel plate, and irradiated with ultraviolet light [illuminance: 200 mW / cm 2 ] at 50 ° C. 2 , Accumulated light intensity: 1000mJ / cm 2 The amount of elution and the degree of swelling of the obtained thin film were measured using an illuminance actinometer (control unit: EYE UV METER UVPF-A2, light receiving unit: EYE UV METER PD-365A2) manufactured by Eye Graphics Co., Ltd. The obtained thin film was a negative electrode protective film. The amount of elution and the degree of swelling of the obtained thin film were measured using the above-mentioned method.
[0085] [Example 2] (Polymerization of Copolymer B) Polymerization was carried out in the same manner as in Example 1, except that a mixture of propylene oxide and allyl glycidyl ether in a molar ratio of 90:10 was used as the epoxide monomer. The structure of the obtained copolymer B was 1 When confirmed by H-NMR, the molar ratio of structural unit (1), structural unit (2), structural unit (3), and structural unit (4) in copolymer B was structural unit (1):structural unit (2):structural unit (3):structural unit (4)=81.7:8.4:8.9:0.9. The number average molecular weight Mn of the resulting copolymer B was 25,000, and the molecular weight distribution Mw / Mn was 1.2.
[0086] (Preparation of thin films) A thin film having a thickness of 10 μm was obtained in the same manner as in Example 1, except that Copolymer B was used.
[0087] [Example 3] (Polymerization of Copolymer C) Polymerization was carried out in the same manner as in Example 1, except that a mixture of propylene oxide and 4-hydroxybutyl acrylate glycidyl ether in a molar ratio of 98:2 was used as the epoxide monomer. The structure of the obtained copolymer C was obtained in the same manner as in Example 1. 1 When confirmed by H-NMR, the molar ratio of structural units (1), structural units (2), structural units (3), and structural units (4) in copolymer C was structural unit (1):structural unit (2):structural unit (3):structural unit (4)=95.0:2.1:2.8:0.1 (see FIG. 4). The number average molecular weight Mn of the resulting copolymer C was 38,000, and the molecular weight distribution Mw / Mn was 1.2.
[0088] (Preparation of thin films) A thin film having a thickness of 10 μm was obtained in the same manner as in Example 1, except that Copolymer C was used.
[0089] [Example 4] (Polymerization of Copolymer D) Polymerization was carried out in the same manner as in Example 1, except that a mixture of propylene oxide and 4-hydroxybutyl acrylate glycidyl ether in a molar ratio of 95:5 was used as the epoxide monomer. The structure of the obtained copolymer D was determined in the same manner as in Example 1. 1 When confirmed by H-NMR, the molar ratio of structural unit (1), structural unit (2), structural unit (3), and structural unit (4) in copolymer D was structural unit (1):structural unit (2):structural unit (3):structural unit (4)=92.3:5.1:2.5:0.1. The number average molecular weight Mn of the resulting copolymer D was 41,000, and the molecular weight distribution Mw / Mn was 1.1.
[0090] (Preparation of thin films) A thin film having a thickness of 10 μm was obtained in the same manner as in Example 1, except that Copolymer D was used.
[0091] [Comparative Example 1] (Preparation of thin films) Polyethylene carbonate (product name "QPAC25", manufactured by EMPOWER MATERIALS) was diluted with chloroform to prepare a solution with a solid concentration of 30% by mass. The prepared solution was applied to the release-treated surface of a release film (manufactured by LINTEC CORPORATION, product name "SP-PET381031") and dried at a temperature of 90°C for 1 minute to obtain a thin film with a thickness of 10 μm.
[0092] [Comparative Example 2] (Preparation of thin films) Polypropylene carbonate (product name "QPAC40", manufactured by EMPOWER MATERIALS) was diluted with ethyl acetate to prepare a solution with a solid concentration of 30% by mass. The prepared solution was applied to the release-treated surface of a release film (manufactured by LINTEC CORPORATION, product name "SP-PET381031") and dried at a temperature of 120°C for 1 minute to obtain a thin film with a thickness of 10 μm.
[0093] [Table 1]
[0094] [Table 2]
[0095] From the results shown in Table 2, it was found that the thin films obtained in Examples 1 to 4 had a small amount of elution despite having a high degree of swelling. This confirmed that the copolymers obtained in Examples 1 to 4 had crosslinking properties. [Explanation of symbols]
[0096] Reference Signs List 10: positive electrode, 11: positive electrode composite layer, 13: positive electrode current collector, 20: negative electrode, 21: negative electrode composite layer, 23: negative electrode current collector, 30: electrolyte layer, 31: separator, 33: electrolyte, 100: battery.
Claims
1. The copolymer includes a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2) in an amount of 0.3 mol % to 20.0 mol %: Resin composition. 【Chemistry 1】 (In the general formula (1) and the general formula (2), R 1 is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; L 1 and L 2 each independently represents a single bond or an alkylene group having 1 to 3 carbon atoms; 1 is a reactive group represented by the following structural formula (2-2): 【Chemistry 2】
2. The resin composition according to claim 1, The copolymer further contains at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (3) and a structural unit represented by the following general formula (4), in an amount of 0.1 mol % to 30.0 mol %: Resin composition. 【Chemistry 3】 (In the general formula (3) and the general formula (4), R 2 is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; L 3 and L 4 each independently represents a single bond or an alkylene group having 1 to 3 carbon atoms; 2 is a reactive group represented by the following structural formula (4-2): 【Chemistry 4】
3. The resin composition according to claim 1 or 2, The crosslinked product of the resin composition is the amount of the copolymer eluted in ethyl acetate is 10% or less; The swelling ratio of the copolymer in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 is 100% or more. Resin composition.
4. The resin composition according to claim 1 or 2 is included. Binder resin.
5. The binder resin according to claim 4, battery.
6. The resin composition according to claim 1 or 2 is included. Polymer thin film.
7. The polymer thin film according to claim 6 , battery.
Citation Information
Patent Citations
Method for preparing crosslinked aliphatic series polycarbonate
CN1775828A
JP1974081498A
Cross-linked material
JP2002275234A
Negative electrode protective film and battery
JP2024146091A
Polymeric binder and all-solid-state secondary battery
WO2020203882A1
Cited By
Metering valve and metering method
KR1020150134367A